History of Japanese art after 1945 institutions, discourse, practice - Kitazawa, Noriaki 1951-; Takemi, Kuresawa; Yuri, Mitsuda (Leuven University Press, 2023)
History of Japanese Art after 1945 surveys the development of art in Japan since WWII. The original Japanese work, which has become essential reading for those with an interest in modern and contemporary Japanese art and is a foundational resource for students and researchers, spans a period of 150 years, from the 1850s to the 2010s. Each chapter is dedicated to a specific period and written by a specialist. The English edition first discusses the formation and evolution of Japanese contemporary art from 1945 to the late 1970s, subsequently deals with the rise of the fine-art museum from the late 1970s to the 1990s, and concludes with an overview of contemporary Japanese art dating from the 1990s to the 2010s. These three parts are preceded by a new introduction that contextualizes both the original Japanese and the English editions and introduces the reader to the emergence of the concept of art (bijutsu) in modern Japan. This English-language edition provides valuable reading material that offers a deeper insight into contemporary Japanese art
"Original title: Bijutsu no Nihon kingendaishi : seido, gensetsu, zōkei. Authorized translation of the chapters 7, 8 and 9 from the Japanese language edition ... © 2014 Japanese language edition by Tokyo Bijutsu Co., Ltd."
Keywords: Geschichte 1945-2010; Geschichte 1970-2000; Kunstmuseum; Kunst; Japan; Art, Japanese / 20th century; Art, Japanese / 21st century; Art and state / Japan / History / 20th century; Art and state / Japan / History / 21st century